Giorgio Agamben's Franciscan Ontology - Chiesa, Lorenzo (Cosmos and History: The Journal of Natural and Social Philosophy, 2009)
This paper analyses Agamben's notion of homo sacer, showing how it should not be confined to the field of a negative critique of biopolitics. In his work, Agamben cautiously delineates a positive figure of homo sacer, whom, according to him, we all virtually are. Such figure would be able to subvert the form in which the relation between bare life and political existence has so far been both thought and lived in the West. How and when is this passage from negative to positive sacredness historically accomplished for Agamben? Is such transit after all thinkable? These are the two basic questions he both unintentionally formulates and leaves undecided in his book Homo Sacer (1995). Agamben further elabourates his investigation of biopolitics in the book he dedicates to Saint Paul, The Time That Remains (2000). Chiesa suggests that, in this volume, the figure of homo sacer as earthly hero is transposed onto that of the messianic man. This can only be achieved by means of an elabourate Christian”and more specifically Franciscan”development of the ontological notion of ‘form of life'. Problematically enough, Agamben is able to carry out a transvaluation of biopolitics only in the guise of a bio-theo-politics.